Gekko aaronbaueri, a new gecko (Squamata: Gekkonidae) from central Laos - Tri, Ngo Van; Thai, Pham Hong; Phimvohan, Anorath; David, Patrick; Teynié, Alexandre (Zootaxa, 2015)
A new species of the genus Gekko Laurenti is described from central Laos. The species is distinguished from its congeners by its moderate size, i.e. maximum SVL 80.0 mm, dorsal pattern of five to six dirty white vertebral spots alternating with yellowish-edged, W-shaped blotches between nape and sacrum and six to seven pairs of dirty white spots interspersed with yellowish-edged dark blotches on the flanks between limb insertions, 0–1 internasal, 39–43 ventral scale rows between the weakly developed ventrolateral folds, 3–4 precloacal pores in males, sometimes separated by one poreless scale, 98–104 smooth dorsal scale rows around the body, 16 broad lamellae beneath digit I of pes, 15–16 broad lamellae beneath digit IV of pes, and enlarged subcaudal scales.